IMPROVEMENT OF METHODOLOGICAL BASIS OF DEVELOPMENT OF RHYTHMIC COMPETENCE IN STUDENTS OF MUSIC EDUCATION - Odilova Gulmira Odilovna (Modern American Journals, 2025)
This article analyzes the issues of improving the methodological foundations of the development of rhythmic competence among students of music education on a scientific basis. The problems of teaching traditional singing and national musical heritage in higher education, ways to solve them, and the effectiveness of using modern pedagogical technologies are considered. The study shows ways to improve the level of professional training of music teachers in traditional singing in the higher pedagogical education system, develop performance skills, as well as develop methodological and practical recommendations. The results emphasize the importance of preserving national culture and stimulating creative abilities in the development of music education.
Keywords: Rhythmic competence, music education, traditional singing, higher education, pedagogical technologies, performance skills, national musical heritage, innovative approaches, educational effectiveness, cultural heritage.